The effects of hedonic, utilitarian and social value on generation Z students’ towards e-shopping intention: a mediating role of e- satisfaction - Haque, A. K. M. Ahasanul; Karim, Wasiul; Ulfy, Mohammad Arije; Anis, Zohurul; Huda, Nazmul (2020)
In recent years, online shopping has dramatically increased and resulted many traditional retail stores a tragic demise. Due to the increasing number of social commerce sites new generations are shifting towards online shopping by preference. The purpose of this study is to investigate the effects of perceived value i.e. hedonic value, utilitarian value and social value, on e-satisfaction and online shopping intention among Generation Z cohort university students. Total 287 data were collected from the students studying at the university in Klang Valley area of Malaysia through online survey and face-to-face conversation. The data were analyzed by using partial least squares structural equation modeling (PLS-SEM). The results show that e-satisfaction have positively and significantly affects online shopping intention. Perceived value such as utilitarian value, hedonic value and social value have significant effects on e- satisfaction and online shopping intention. The findings of this research will be extremely important for both digital marketers and service providers to establish effective strategies to meet new generations’ expectation. Hence, study will enhance the researchers’ ability to discover more variables to examine the satisfaction and intention to use particular sites for e-shopping.